2011
DOI: 10.1007/s00296-011-1992-x
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of TPP1 in fibroblast-like synovial cells might be involved in the pathogenesis of rheumatoid arthritis

Abstract: We undertook this study to determine whether the altered expression of telomeric proteins TPP1 and POT1 in fibroblast-like synovial cells (FLS) could provide insights into the pathogenesis of rheumatoid arthritis (RA). FLS were isolated from patients with RA, osteoarthritis (OA) and traumatic joint disease, and cultured in vitro. TPP1 and POT1 mRNA level of FLS were measured using real-time quantitative polymerase chain reaction (RT-qPCR) in 42 RA, 23 OA and 13 healthy cases. Immunofluorescence staining and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The TPP1 gene is one of the top network genes and ranked the first on GS. TPP1 gene was associated with rheumatoid arthritis (RA) [21], which suggested that TPP1 may be a potential candidate gene for T1D, as T1D and RA were reported to have some common susceptibility loci [22]. In addition, TPP1 may indirectly influence metabolism possibly by regulating telomere length [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPP1 gene is one of the top network genes and ranked the first on GS. TPP1 gene was associated with rheumatoid arthritis (RA) [21], which suggested that TPP1 may be a potential candidate gene for T1D, as T1D and RA were reported to have some common susceptibility loci [22]. In addition, TPP1 may indirectly influence metabolism possibly by regulating telomere length [23].…”
Section: Resultsmentioning
confidence: 99%
“…As described above, TPP1 and SKAP2 showed co-expression relationship with each other, thus TPP1 may be also associated with T1D. A study of RA has found that decreasing expression of TPP1 was observed in RA patients and it had a negative correlation with autoantibodies [21]. T1D and RA are two auto-immunity disease and were reported to share some susceptibility loci, such as SKAP2 [22].…”
Section: Discussionmentioning
confidence: 99%
“…17 Similar finding are suggested by various studies done so far. 5,18,19,20,21,22,23 Increased levels of the ferritin causes formation of the free radicals, which damages cellular organelles, especially mitochondria. 9 This impairs β-oxidation of fatty acids in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…TPP-1 may not only be a promising target for further research in the field of neurology. Some recent studies show a potential role of this particle in the pathogenesis of rheumatoid arthritis, as TPP-1 altered expression in fibroblast-like synovial cells was associated with development of this rheumatic disease [ 10 ].…”
Section: Discussionmentioning
confidence: 99%